THE ROLE OF THE LEADER, MENTOR TEACHER AND PERSONAL DEVELOPMENT OPPORTUNITIES IN THE BIPOLAR MENTOR RELATIONSHIP - Rinyuné Ökrös, Mónika; Ökrös, Csaba; Bíró, Melinda (Stadium - Hungarian Journal of Sport Sciences, 2023)
During the mentoring work, the question often arises as to how much the mentor becomes a model for the student or intern. What could be the reason why some people reflect the values and models that they represent and thus the students follow and respect them, just by their activities, by the manifestation of their personality, by their existence within the entire school? How can the mentoring task be made more effective? Answering these questions motivated me to prepare the research, the purpose of which is to determine the role of the mentor teacher in the mentoring process and to demonstrate the criteria for the success and efficiency of the mentor-student relationship. To answer the research questions, we conducted a questionnaire survey. In the study, we interviewed teachers and mentor teachers (n=30), of whom 63% were women, 36.7% were men (average age 51, minimum: 38, maximum: 65). 66.7% have more than 20 years of teaching experience. 11.9% of the respondents teach in the field of physical education and sports literacy. Our results showed that the lead and mentor teacher has a decisive role in the mentoring process and his personal influence can be an important factor in the retention of teacher candidates. In the mentoring process, openness to the new, mutual respect and critical, empathetic mentoring behavior are the most encouraging in the bipolar mentoring relationship. Students' self-confidence is increased most by the teacher's encouraging behavior based on professional knowledge. In terms of their own development, mentors are mostly inspired by students with a cooperative, positive attitude, but they are at least as motivated by the student's interest in teaching and becoming a teacher. It is interesting that it is not the powerful managerial control, but the developmental mentoring control that assumes reflexivity that appears during the teachings.